Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Xie Chiang, Mandi (2018)
Hereby, we study the Fast Retailing group, belonging to the fast fashion textile industry, located in the third place worldwide, after Zara (Inditex) and H&M. Among the diverse brands that compose this industry, we find UNIQLO, GU, PTT, CDC, among others; however, none of them has entered the Peruvian market yet, that is why through the research carried out at a macro and micro level, we propose an adequate strategy to enter this market. Fast Retailing with its most representative brand, UNIQLO, should enter the country through a wholly owned subsidiary, thus exercising control over all processes, ensuring its efficiency and the high quality in their garments. If this strategy is applied, it would be widely accepted by consumers, because it offers high quality and durability in their garments based on the use of technologies and at affordable prices. Likewise, it is recommended that Fast Retailing improve the time it takes to launch garments as it can take up to 12 months, while Inditex can do it in 3 weeks. Similarly, it should expand geographically to more countries with the aim of entering new markets and positioning itself as a brand.